High‐throughput genotyping of single‐nucleotide polymorphisms in ace‐1 gene of mosquitoes using MALDI‐TOF mass spectrometry. (12th June 2012) - Mao, Yun; Tan, Feng; Yan, Shuai‐Guo; Wu, Guo‐Xing; Qiao, Chuan‐Ling; Zhang, Wen‐Xue; Cui, Feng
Abstract : Abstract Acetylcholinesterase (AChE) plays a vital role in the nervous system of insects and other animal species and serves as the target for many chemical agents such as organophosphate and carbamate insecticides. The mosquito, Culex pipiens complex, a vector of human disease, has evolved to be resistant to insecticides by a limited number of amino acid substitutions in AChE1, which is encoded by the ace‐1 gene. The aims of this study are to identify single nucleotide polymorphism (SNP) sites in the ace‐1 gene of the C. pipiens complex and explore an economical high‐throughput method to differentiate the genotypes of these sites in mosquitoes collected in the field. We identified 22 SNP sites in exon regions of the ace‐1 gene. Four of them led to non‐synonymous mutations, that is, Y163C, G247S, C677S and T682A. We used matrix‐assisted laser desorption ionization – time‐of‐flight mass spectrometry for genotyping at these four sites and another site F416V, which was relevant to insecticide resistance, in 150 mosquitoes collected from 15 field populations. We were able to synchronize analysis of the five SNP sites in each well of a 384‐well plate for each individual mosquito, thus decreasing the cost to one‐fifth of the routine analysis. Heterozygous genotypes at Y163C and G247S sites were observed in one mosquito. The possible influence of the five SNP sites on the activity or function of the enzyme is discussed based on the predicted tertiary structure of the enzyme.